2018
DOI: 10.1055/a-0574-2396
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of features of chronic pancreatitis during endoscopic ultrasound-based surveillance of individuals at high risk for pancreatic cancer

Abstract: Background and study aims  During endoscopic ultrasound (EUS)-based pancreatic ductal adenocarcinoma (PDAC)-surveillance in asymptomatic individuals, features of chronic pancreatitis (CP) are often detected. Little is known about the prevalence and progression of these features. The aim of this study was to quantify these features, assess the interobserver agreement, assess possible associated factors, and assess the natural course during 3 years of follow-up. Patients and methods  Two experienced endosonograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
(28 reference statements)
0
7
0
Order By: Relevance
“…However, in only a minority of patients are these findings identified, and our current understanding of evolution of pancreatic precursors suggests that more subtle findings, such as parenchymal changes, can be important to recognize precursors. 28,29 Most of these parenchymal changes were initially described in relation to chronic pancreatitis-associated changes, but have since been associated with changes observed in neoplastic progression. 28,30 Improved resolution of B-mode EUS imaging and enhanced imaging modalities (ie, elastography and contrast enhancement) will likely further improve our ability to characterize parenchymal changes associated with early neoplastic development.…”
Section: Standardization Of Endoscopic Ultrasoundmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in only a minority of patients are these findings identified, and our current understanding of evolution of pancreatic precursors suggests that more subtle findings, such as parenchymal changes, can be important to recognize precursors. 28,29 Most of these parenchymal changes were initially described in relation to chronic pancreatitis-associated changes, but have since been associated with changes observed in neoplastic progression. 28,30 Improved resolution of B-mode EUS imaging and enhanced imaging modalities (ie, elastography and contrast enhancement) will likely further improve our ability to characterize parenchymal changes associated with early neoplastic development.…”
Section: Standardization Of Endoscopic Ultrasoundmentioning
confidence: 99%
“…28,29 Most of these parenchymal changes were initially described in relation to chronic pancreatitis-associated changes, but have since been associated with changes observed in neoplastic progression. 28,30 Improved resolution of B-mode EUS imaging and enhanced imaging modalities (ie, elastography and contrast enhancement) will likely further improve our ability to characterize parenchymal changes associated with early neoplastic development. An obvious parallel to draw on is the unequivocal benefit of high-resolution white light and virtual chromoendoscopy in detection of gastric and colonic neoplasia in luminal imaging.…”
Section: Standardization Of Endoscopic Ultrasoundmentioning
confidence: 99%
“…The supposed explanation is that multifocal PanIN lesions produce obstructive lobular atrophy, which is probably the source of CPis[53]. Features of chronic pancreatitis during EUS-based surveillance of HRI are easily seen with good interobserver agreement[48]. One study showed that CPis generally have no or little progression over time, although the follow-up period was limited (3 years)[48].…”
Section: Place Of Endoscopic Ultrasound For Pancreatic Screening Of Hmentioning
confidence: 99%
“…Features of chronic pancreatitis during EUS-based surveillance of HRI are easily seen with good interobserver agreement[48]. One study showed that CPis generally have no or little progression over time, although the follow-up period was limited (3 years)[48]. A fatty pancreas has also been reported to be a risk factor for PC and should be noted on the EUS report[55].…”
Section: Place Of Endoscopic Ultrasound For Pancreatic Screening Of Hmentioning
confidence: 99%
See 1 more Smart Citation